2021
DOI: 10.3847/1538-3881/abf9a8
|View full text |Cite
|
Sign up to set email alerts
|

Observations with the Differential Speckle Survey Instrument. X. Preliminary Orbits of K-dwarf Binaries and Other Stars

Abstract: This paper details speckle observations of binary stars taken at the Lowell Discovery Telescope, the WIYN telescope, and the Gemini telescopes between 2016 January and 2019 September. The observations taken at Gemini and Lowell were done with the Differential Speckle Survey Instrument (DSSI), and those done at WIYN were taken with the successor instrument to DSSI at that site, the NN-EXPLORE Exoplanet Star and Speckle Imager (NESSI). In total, we present 378 observations of 178 systems, and we show that the un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
0
18
2
Order By: Relevance
“…These uncertainties were propagated throughout our analysis described in Section 3.4. These values are slightly larger than those derived in Horch et al (2017), Colton et al (2021), or Horch et al (2021); this is likely due to the faintless of our targets, and the filterless observations that took place during the April 2017 observing run. In general, filterless observations reduce the precision of our astrometry, but allow us to observe fainter companions.…”
Section: New Discoveriescontrasting
confidence: 64%
See 3 more Smart Citations
“…These uncertainties were propagated throughout our analysis described in Section 3.4. These values are slightly larger than those derived in Horch et al (2017), Colton et al (2021), or Horch et al (2021); this is likely due to the faintless of our targets, and the filterless observations that took place during the April 2017 observing run. In general, filterless observations reduce the precision of our astrometry, but allow us to observe fainter companions.…”
Section: New Discoveriescontrasting
confidence: 64%
“…We assume that the calibrations from Horch et al (2021) are also appropriate for this work, given that our targets were observed on the same runs, besides those observed in February 2020. Figure 3 of Horch et al (2021) shows the derived uncertainties from the known orbital elements that we have incorporated into our analysis. However, Horch et al (2021) did not include data from February 2020.…”
Section: Observational Routinementioning
confidence: 99%
See 2 more Smart Citations
“…Their ephemeris positions are computed based on the orbital elements, and their scale and orientation are derived from these results. We assume that the calibrations from Horch et al (2021) are also appropriate for this work, given that our targets were observed on the same runs, besides those observed in February 2020. Figure 3 of Horch et al (2021) shows the derived uncertainties from the known orbital elements that we have incorporated into our analysis.…”
Section: Observational Routinementioning
confidence: 99%